Atmospheric pressure chemical vapour deposition growth of graphene for the synthesis of SiO2 based graphene ball - Nurkhaizan Zulkepli,; Jumril Yunas,; Mohd Ambri Mohamed,; Mohamad Shukri Sirat,; Azrul Azlan Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Graphene is a prominent carbon nanomaterial with fascinating characteristics such as high conductivity and very high charge carrier mobility at low temperatures. Numerous synthesis methods for graphene have been established. Chemical vapour deposition (CVD) is among the most successful methods to fabricate high-quality graphene. However, metal-catalyzed growth is used in virtually all of the CVD techniques mentioned. To remove these metal catalysts and relocate the graphene to the necessary dielectric substrate (SiO2/Si or quartz), complex and sophisticated post-growth methods must be used, which limits the usage of graphene in practical electronic components. In the present work, we conducted a preliminary study to determine the suitable methane(CH4) flowrate, which could be used to synthesise SiO2 based graphene ball. Few-layer graphene was grown on a large area of copper(Cu) surface using 20 sccm CH4 in atmospheric pressure CVD (APCVD). The influence of CH4 flowrate on graphene growth has been investigated. Graphene was deposited on a metal catalyst substrate at optimum temperatures of 1000 °C.